Helical tomotherapy for spine oligometastases from gastrointestinal malignancies - Choi, Yunseon (The Korean Society for Radiation Oncology, 2011)
PURPOSE: This study evaluated the treatment effectiveness and proper radiation dose of helical tomotherapy (HT) in spine oligometastases from gastrointestinal cancers. MATERIALS AND METHODS: From 2006 to 2010, 20 gastrointestinal cancer patients were treated with HT for spine oligometastases (31 spine lesions). The gross tumor volume (GTV) was the tumor evident from magnetic resonance imaging images fused with simulation computed tomography images. Clinical target volume (CTV) encompassed involved vertebral bodies or dorsal elements. We assumed that the planning target volume was equal to the CTV. We assessed local control rate after HT for 31 spine metastases. Pain response was scored by using a numeric pain intensity scale (NPIS, from 0 to 10). RESULTS: Spine metastatic lesions were treated with median dose of 40 Gy (range, 24 to 51 Gy) and median 5 Gy per fraction (range, 2.5 to 8 Gy) to GTV with median 8 fractions (range, 3 to 20 fraction). Median biologically equivalent dose (BED, α/β = 10 Gy) was 52 Gy(10) (range, 37.5 to 76.8 Gy(10)) to GTV. Six month local control rate for spine metastasis was 90.3%. Overall infield failure rate was 15% and outfield failure rate was 75%. Most patients showed pain relief after HT (93.8%). Median local recurrence free survival was 3 months. BED over 57 Gy(10) and oligometastases were identified as prognostic factors associated with improved local progression free survival (p = 0.012, p = 0.041). CONCLUSION: HT was capable of delivering higher BED to metastatic lesions in close proximity of the spinal cord. Spine metastases from gastrointestinal tumors were sensitive to high dose radiation, and BED (α/β = 10 Gy) higher than 57 Gy(10) could improve local control.